Do dogs rescue their owners from a stressful situation? A behavioral and physiological assessment - Carballo Pozzo Ardizzi, Fabricio (2020)
Rescue behavior is considered a type of pro-social response, defined as a voluntary action directed to benefit another individual who is in a stressful or dangerous situation. In two experiments, we investigated whether dogs would rescue their owners when the person was trapped inside a wooden box and emitted clear signs of stress. The performance of these dogs was compared against that of a control group in which the owners remained calm while trapped. In addition, to assess if training modulated this behavior, we tested a group of dogs from the military trained in search and rescue tasks (Experiment 1). Results showed that dogs opened the box more frequently when the owner pretended to be stressed than when calm. Training shortened latencies to open the door but not the frequency of the behavior. In Experiment 2, we investigated if emotional contagion could be a possible mechanism underlying dogs' rescue responses by measuring dogs’ behavior, heart rate, and saliva cortisol level in the stressed and calm conditions, and also controlled for obedience by having the calm owners call their pets while trapped. We replicated the findings of Experiment 1 as more dogs opened the door in the stressed owner condition than in the calm condition. In addition, we observed an increase in heart rate across trials in the stressed condition and a decrease across trials in the calm condition, but no differences in cortisol levels or stress-related behaviors between conditions. In brief, we found evidence that approximately half of the dogs without previous training showed spontaneous rescue behaviors directed to their owners. Neither was this behavior motivated by obedience nor by the motivation to re-establish social contact with the owner. We conclude that emotional contagion is a plausible mechanism underlying dogs’ rescue behavior in the present protocol.